Characteristics and Pathways of Long-Stay Patients in High and Medium Secure Settings in England; A Secondary Publication From a Large Mixed-Methods Study - Völlm, Birgit A.; Edworthy, Rachel; Huband, Nick; Talbot, Emily; Majid, Shazmin; Holley, Jessica; Furtado, Vivek; Weaver, Tim; McDonald, Ruth; Duggan, Conor (Frontiers in Psychiatry, 2018)
Background: Many patients experience extended stays within forensic care, but the characteristics of long-stay patients are poorly understood. Aims: To describe the characteristics of long-stay patients in high and medium secure settings in England. Method: Detailed file reviews provided clinical, offending and risk data for a large representative sample of 401 forensic patients from 2 of the 3 high secure settings and from 23 of the 57 medium secure settings in England on 1 April 2013. The threshold for long-stay status was defined as 5 years in medium secure care or 10 years in high secure care, or 15 years in a combination of high and medium secure settings. Results: 22% of patients in high security and 18% in medium security met the definition for ‘long-stay’, with 20% staying longer than 20 years. Of the long-stay sample, 58% were violent offenders (22% both sexual and violent), 27% had been convicted for violent or sexual offences whilst in an institutional setting, and 26% had committed a serious assault on staff in the last 5 years. The most prevalent diagnosis was schizophrenia (60%) followed by personality disorder (47%, predominantly antisocial and borderline types); 16% were categorised as having an intellectual disability. Overall, 7% of the long-stay sample had never been convicted of any offence, and 16.5% had no index offence prompting admission. Although some significant differences were found between the high and medium secure samples, there were more similarities than contrasts between these two levels of security. The treatment pathways of these long-stay patients involved multiple moves between settings. An unsuccessful referral to a setting of lower security was recorded over the last 5 years for 33% of the sample. Conclusions: Long-stay patients accounted for one fifth of the forensic inpatient population in England in this representative sample. A significant proportion of this group remain unsettled. High levels of personality pathology and the risk of assaults on staff and others within the care setting are likely to impact on treatment and management. Further research into the treatment pathways of longer stay patients is warranted to understand the complex trajectories of this group.